'Under The Breath of Asia': Echoes of the 1917 Revolution in French-Speaking Belgium. Issue 1 (2nd January 2019) - Čečović, Svetlana
Abstract : This article studies the images of Russia in French-speaking Belgium after 1917. It focuses on a number of Belgian intellectuals and travellers to Russia: the socialist politician Jules Destrée; the journalist Pierre Daye who sympathized with fascism; Charles Sarolea, the Belgian consul in Edinburgh and a propagandist of the Belgian cause; the famous literary critic Louis Dumont-Wilden; and the (French) Jesuit Bishop Michel d'Herbigny, who operated from Belgium. They all comply with the reigning Western image of Russia as the 'fundamental other' (E.Adamovsky). However, despite the domination of clichés, Russia after 1917 was not only a timeless and unchangeable object of imagination. Russian émigrés such as princess Zinaida Schakhovskoy and the translator and critic Benjamin Goriély tried to overcome the polarization between Russia and the West and offer a conciliatory voice.